2023
DOI: 10.2147/jpr.s392868
|View full text |Cite
|
Sign up to set email alerts
|

Postural Control of Patients with Low Back Pain Under Dual-Task Conditions

Abstract: Low back pain is a major global public health problem, but the current intervention effect is not ideal. A large body of previous literature suggests that patients with chronic low back pain may have abnormal postural control, which is more evident in the dual task situation. In recent years, research on postural control in patients with low back pain under dual-task conditions has gradually become a hot topic. However, the results obtained from these studies were not entirely consistent. In this review, we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Previous studies using a dual-task interference paradigm to investigate postural control in individuals with LBP have reported inconclusive results. Xiao et al [ 17 ] proposed multiple factors that could affect postural control among patients with LBP when performing dual-task activities. However, there are two crucial factors that need to be considered in maintaining postural stability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies using a dual-task interference paradigm to investigate postural control in individuals with LBP have reported inconclusive results. Xiao et al [ 17 ] proposed multiple factors that could affect postural control among patients with LBP when performing dual-task activities. However, there are two crucial factors that need to be considered in maintaining postural stability.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are two crucial factors that need to be considered in maintaining postural stability. The first factor is sensory strategies which have a significant role in maintaining postural stability [ 17 ]. When proprioceptive information from the ankle is reliable, individuals tend to rely on ankle strategy for postural control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tele-rehabilitation technology based on mobile health (m-health) has experienced rapid development, especially during the COVID-19 outbreak [13] . This technology enables patients to receive exercise instructions through mobile devices and engage in rehabilitation treatment anytime and anywhere [14] .Our preliminary exploratory study has indicated that core stability training instruction provided remotely has the potential to improve lower back function and reduce pain intensity in patients with chronic low back pain [15] .Research has demonstrated that remote education and exercise guidance via videoconferencing hold promise in achieving therapeutic effects [16] .However, these interventions have not provided patients with objective and accurate supervision and exercise guidance in their homes.Research has shown that unsupervised app-based treatments have not demonstrated signi cant treatment e cacy and costeffectiveness [17] .…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%